An Analysis of China's Muslim-Related Policies from the Perspectives of Ethnic Heterogeneity, Sinicization and "Anxiety Management". Issue 1 (16th June 2022) - Zhang, Bozhen
Abstract : As an officially atheist country led by the Communist Party, China is often regarded as a nation where citizens' freedom of religion is infringed. Despite its status as one of the five officially recognized religions in China, Islam is regarded extremely vulnerable in front of the state, as is shown by the country's controversial policies towards its Uyghur Muslims. It is even common to hear scholars, politicians, and media labeling China as "anti-Islam." Most research simply regards China's Muslim-related policies as unitary, ignoring the diversity of China's Muslim communities and the basic logics behind these policies. This article will analyze China's Muslim-related policies based on the actual situation of ethnic heterogeneity (mainly the Hui and Uyghurs) and the central principles of Sinicization and promoting ethnic harmony. It will argue that China's Muslim-related policies may sometimes seem like hasty "anxiety management" and may appear objectionable from a Western-liberal perspective, but they are not ill-intended and cannot simply be dichotomized as "anti-Islam."